FIELD TEST PERFORMANCE OF HYDRAULIC SHORING WITH PLYWOOD SHEETING IN A SOFT AND SENSITIVE CLAY (Global Journal of Advanced Engineering Technologies and Sciences, 2021)
This paper presents the results of a field experimental case study carried out to investigate the performance of vertical aluminum hydraulic shoring with plywood sheeting in a soft and sensitive clay trench. Installation, instrumentation, and field test procedures are presented for this type of vertical aluminum hydraulic shoring with plywood sheeting (speed shoring) in conformity with United States OSHA guidelines and placed inside the trench to cover the total 2.4 m (8 ft) depth of excavation. The field test results are presented in terms of soil pressure distribution along the depth of excavation with and without a 30-kPa surface surcharge load next to the edge of one side of the trench. The results reveal the potential use of this type of shoring in an excavation or trench in this type of soil.